Navigation and Robotics in Total Joint and Spine Surgery - Stiehl, James B.; Konermann, Werner H.; Haaker, Rolf G. (Springer Berlin Heidelberg, 2004)
This book reviews the recent international experience with the applications of computer assisted orthopaedic surgery in clinical practice. Recent decades of the human condition have witnessed the dramatic evolution of technology and the application to everyday existence. The ability to use such innovation in surgical practice is now easily within our grasp. Though clinical experience is short term, as will be demonstrated the problems are finite and limited only by the need for refinement. We can now clearly state that current surgical practice will be revolutionized by these new methodologies. This edition is all encompassing for musculoskeletal surgery including the spine, trauma, sports, and reconstructive surgery. Because of its simplicity, computer navigation will be an early tool in such areas as total joint replacement, anterior cruciate ligament reconstruction, and placement of pedicle screws in complex spinal surgery. New techniques in Minimally Invasive Surgery will require the precision and digital "surgical exposure" offered by the computer. However, we anticipate in a few years, that robotics with computer activated technology will rise to an important role for the practicing surgeon. Surgeons who are comfortable with technology and yearn for better solutions with their techniques will benefit from the knowledge of this experience. Americans at the AAOS 2003 annual meeting in New Orleans, have now joined the wave of enthusiasm for computer assisted orthopaedic surgery (CAOS) as well as the exciting new vistas of Minimally Invasive Surgery.